Long-Term Physical Activity Participation and Subsequent Incident Type 2 Diabetes Mellitus: A Population-Based Cohort Study - Li, Chenglong; Ma, Yanjun; Hua, Rong; Zheng, Fanfan; Xie, Wuxiang (Frontiers in Endocrinology, 2021)
Background Uncertainty remains concerning association between long-term physical activity and incident type 2 diabetes mellitus (DM). We intended to evaluate physical activity participation over a 6-year span and assess association with subsequent 10-year incident DM risk, as well as examine mediation role by obesity. Methods A total of 9757 community-dwelling adults aged ≥ 50 years in England were included in the population-based cohort. Physical activity participation, including trajectories and cumulative participation were assessed using weighted Z score over a 6-year span from wave 1 (2002–2003) to wave 4 (2008–2009). Incident DM recorded over a 10-year span from wave 4 (2008–2009) to wave 9 (2018–2019) was outcome. Results 5 distinct activity trajectories were identified, including persistently low (N=3037, incident DM=282), initially low then improving (1868, 90), initially high then declining (325, 20), persistently moderate (2489, 170), and persistently high (2038, 108). Compared with persistently low, participants of initially low then improving, persistently moderate and high were associated with lower incident DM risk, with multivariable-adjusted hazard ratios (HR) of 0.41 (95% confidence interval [CI]: 0.32 to 0.53, P<0.001), 0.70 (95% CI: 0.56 to 0.89, P=0.004) and 0.49 (95% CI: 0.37 to 0.65, P <0.001), respectively. Elevated cumulative activity was also associated with lower DM risk, with each quintile increment in cumulative weighted Z score corresponding to HR of 0.76 (95% CI: 0.71 to 0.82, P <0.001). Mediation analysis found that body mass index, waist circumference and change in body mass index mediate 10% (P <0.001), 17% (P <0.001) and 9% (P <0.001) of the observed association between activity and incident DM, respectively. Conclusions For middle aged and older adults, both gradually improved and persistently active participation in physical activity were associated with subsequent lower risk of incident DM, with obesity playing a potential mediator. Strategies focusing on improving and maintaining active participation in physical activity might be beneficial from DM prevention perspective.